Marketing and social media : a guide for libraries, archives, and museums - Mon, Lorri M., 1963- (Bloomsbury Academic, 2025)
Marketing and Social Media: A Guide for Libraries, Archives, and Museums is a much-needed guide to marketing for libraries, archives, and museum professionals in the social media age. This book is both an introductory textbook and a guide for working professionals on developing a comprehensively planned marketing campaign that integrates social media into a holistic marketing strategy. Beginning with mission, goals, and objectives, readers will put together working knowledge of the essential components for planning a marketing campaign. Chapters cover how to do a strengths, weaknesses, opportunities and threats (SWOT) analysis, identify and involve stakeholders, a 4-step marketing model, market research, market segmentation, market mix strategy, and evaluation. The final chapter, “From the Social Media Manager's Perspective: Putting it all Together,” guides readers through first days on the job of taking over an organization's social media marketing efforts, and the steps to be taken in the first days, weeks, and months that follow, including promotional and assessment activities.